New Delivery Systems of Stem Cells for Vascular Regeneration in Ischemia - Fakoya, Adegbenro Omotuyi John (Frontiers in Cardiovascular Medicine, 2017)
The finances of patients and countries are increasingly overwhelmed with the plague of cardiovascular diseases as a result of having to chronically manage the associated complications of ischemia such as heart failures, neurological deficits, chronic limb ulcers, gangrenes, and amputations. Hence, scientific research has sought for alternate therapies since pharmacological and surgical treatments have fallen below expectations in providing the desired quality of life. The advent of stem cells research has raised expectations with respect to vascular regeneration and tissue remodeling, hence assuring the patients of the possibility of an improved quality of life. However, these supposed encouraging results have been short-lived as the retention, survival and engraftment rates of these cells appear to be inadequate, hence, the long-term beneficial effects of these cells cannot be ascertained. These drawbacks have led to the relentless research into better ways to deliver stem cells or angiogenic factors (which mobilize stem cells) to the regions of interest to facilitate increased retention, survival, engraftment and regeneration. This review considered methods such as the use of scaffolds, retrograde coronary delivery, improved combinations, stem cell pretreatment, preconditioning, stem cell exosomes, mannitol, magnet, and ultrasound-enhanced delivery, homing techniques and stem cell modulation. Furthermore, the study appraised the possibility of a combination therapy of stem cells and macrophages, considering the enormous role macrophages play in repair, remodeling, and angiogenesis.